Mononuclear cell composition and activation in blood and mucosal tissue of eosinophilic esophagitis - Gruden, Eva; Kienzl, Melanie; Ristic, Dusica; Kindler, Oliver; Kaspret, David Markus; Schmid, Sophie Theresa; Kargl, Julia; Sturm, Eva; Doyle, Alfred D.; Wright, Benjamin L.; Baumann-Durchschein, Franziska; Konrad, Julia; et al. (Frontiers in Immunology, 2024)
Eosinophilic esophagitis (EoE) is a chronic, inflammatory, antigen-driven disease of the esophagus. Tissue EoE pathology has previously been extensively characterized by novel transcriptomics and proteomic platforms, however the majority of surface marker determination and screening has been performed in blood due to mucosal tissue size limitations. While eosinophils, CD4 + T cells, mast cells and natural killer (NK) T cells were previously investigated in the context of EoE, an accurate picture of the composition of peripheral blood mononuclear cells (PBMC) and their activation is missing.In this study, we aimed to comprehensively analyze the composition of peripheral blood mononuclear cells and their activation using surface marker measurements with multicolor flow cytometry simultaneously in both blood and mucosal tissue of patients with active EoE, inactive EoE, patients with gastroesophageal reflux disease (GERD) and controls. Moreover, we set out to validate our data in co-cultures of PBMC with human primary esophageal epithelial cells and in a novel inducible mouse model of eosinophilic esophagitis, characterized by extensive IL-33 secretion in the esophagus.Our results indicate that specific PBMC populations are enriched, and that they alter their surface expression of activation markers in mucosal tissue of active EoE. In particular, we observed upregulation of the immunomodulatory molecule CD38 on CD4 + T cells and on myeloid cells in biopsies of active EoE. Moreover, we observed significant upregulation of PD-1 on CD4 + and myeloid cells, which was even more prominent after corticosteroid treatment. With co-culture experiments we could demonstrate that direct cell contact is needed for PD-1 upregulation on CD4 + T cells. Finally, we validated our findings of PD-1 and CD38 upregulation in an inducible mouse model of EoE.Herein we show significant alterations in the PBMC activation profile of patients with active EoE in comparison to inactive EoE, GERD and controls, which could have potential implications for treatment. To our knowledge, this study is the first of its kind expanding the multi-color flow cytometry approach in different patient groups using in vitro and in vivo translational models.